MEASUREMENT OF CORTISOL IN HUMAN PLASMA AND URINE BY ULTRA PERFORMANCE LIQUID CHROMATOGRAPHY-TANDEM MASS SPECTROMETRY - Alvi, Syed N; M Hammami, Muhammad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to develop and validate a simple, sensitive, specific, and rapid assay for quantification of clinically relevant cortisol level in human plasma and urine samples. Methods: Ultra performance liquid chromatographic-tandem mass spectrometric (UPLC-MS/MS) analysis was performed on Atlantis dC18 column (2.1×100 mm, 3 μm) with a mobile phase consisting of acetonitrile and 2 mM ammonium acetate (50:50, v: v) that was delivered at a flow rate of 0.3 ml/min. Tolperisone (2 ng) was used as an internal standard (IS). Biological samples were extracted with a mixture of hexane and methyl tert-butyl ether (8:2, v: v). The eluents were monitored using electrospray ionization in the positive ion mode with transition mass to charge ratio set at 363.1 → 121.0 and 246.0 → 97.9 for cortisol and IS, respectively. The method was validated according to international guidelines. Results: Retention times of cortisol and IS were about 1.4 and 2.3, respectively. Relationship between cortisol level and peak area ratio of cortisol to IS was linear (R2≥0.987) in the range of 2.5–400 ng/ml and 1.0–200 ng/ml in plasma and urine samples, respectively. Intra- and inter-day coefficient of variation and bias were ≤9.7% and ±11.1%, and ≤10.4% and ±11.5% for plasma and urine samples, respectively. Extraction recoveries were in 80–91% for cortisol plasma and 80–86% for cortisol in urine samples. Cortisol was ≥86% stable when stored at room temperature for 24 h or at −20°C for 24 weeks in plasma samples and ≥93% stable when stored at room temperature for 24 h or −20°C for 16 weeks in urine samples. Conclusion: We report a validated, clinically relevant, simple, and rapid UPLC-MS/MS assay of cortisol level in human plasma and urine.